Priority-based routing and wavelength assignment algorithm of multi-objective in WDM network - Xiang-xuan TIAN; Jun-gang YANG; Ya-liang CHE; Wen-zheng SUN; Gu-jing LIU (Tongxin xuebao)
An effective algorithm aiming at the multi-objective routing and wavelength assignment through priority in dynamic WDM optical network was proposed.The objective of the design is to maximize the number of accepted communication requests subjected to a limited number of wavelength channels.The relation between path type was adopted and the traffic volume was used to determine the priority of the connection requests,and the network state was incorporated into the routing decisions and wavelength assignment.The simulation results conclusively demonstrate that the proposed algorithm can greatly improve the blocking performance and utilization of the optical network resource.